Disaster! - McIntosh M. Mary (Oxford Bookworms Factfiles Level 4)
Every day a disaster strikes somewhere in the world. As we watch disasters on television and read about them in the newspapers, we feel a mixture of fascination and fear. Some disasters have always been with us: earthquakes, volcanoes, tornadoes and floods are as common today as they were in the past. Others, like the nuclear disaster of Chernobyl, are the result of our own technology. This book looks at both types of disaster, and at what we can learn from them.